Description of families affected by fire disaster in Jayapura city area - Iribaram, Ibrahim Ismail; Bouway, Dolfinus; Tuturop, Katarina L; Wakum, Arnold; Tappy, Melkior; Adimuntja, Natalia Paskawati (Journal of Midwifery and Nursing, 2024)
Fire disasters are always unpredictable and unpredictable. Fires often cause various undesirable consequences both concerning material losses, business activities, environmental damage, and pose a threat to the safety of human life. Fires can cause life-threatening impacts and material and social losses, so this shows the need for increased vigilance in fire prevention. The causes of fires in Jayapura City can be caused by natural and non-natural factors. The purpose of this study was to determine the description of families affected by fire disasters in Jayapura City. This type of research is survey research. With the approach used in this research is descriptive quantitative. The population in this study were 73 respondents (KK) affected by fire disasters in Jayapura City in 2022 and a sample of 73 samples with accidental sampling technique. Data were obtained using a questionnaire and analysed using univariate analysis. The results of univariate analysis showed the characteristics of respondents who were male (64.4%), aged <40 years (57.5%), high school education (SMA) (47.9%). The results of the study according to the variables of knowledge level, experience and preparedness were less knowledgeable as many as 24 respondents (32.9%), had less experience as many as 54 respondents (74.0%), and less preparedness as many as 48 respondents (65.8%).